contestada

Question 13
<
Given the function C(t) = (t – 6)(t + 1)(t – 7)
its C-intercept is=
I
its t-intercepts are =

Respuesta :

Answer:

The c intercept is 42

The t intercepts are: 6, -1 and 7

Step-by-step explanation:

Given

[tex]c(t) = (t - 6)(t +1)(t-7)[/tex]

Solving (a): The c intercept

Simply set t to 0

[tex]c(t) = (t - 6)(t +1)(t-7)[/tex]

[tex]c(0) = (0 - 6)(0 +1)(0-7)[/tex]

[tex]c(0) = (- 6)(1)(-7)[/tex]

[tex]c(0) = 42[/tex]

Solving (b): The t intercept

Simply set c(t) to 0

[tex]c(t) = (t - 6)(t +1)(t-7)[/tex]

[tex](t - 6)(t +1)(t-7) = 0[/tex]

Split

[tex]t - 6= 0,\ \ t +1= 0,\ \ t-7 = 0[/tex]

Solve for t

[tex]t = 6,\ \ t =-1,\ \ t=7[/tex]